META-ANALYSIS REVIEW OF THE USE OF VIRTUAL REALITY IN SAFETY TRAINING - Ariyanto, Stefanus Timonora Wahyu; Noviah, Ema; Riyadi, Riyadi; Sarifah, Iva (International Journal of Business, Law, and Education, 2023)
This study aims to review the use of virtual reality in safety training through a meta-analysis approach. The choice of topics in this study was motivated by the lack of studies related to correlations that discuss Virtual Reality" and "safety amid the high use of Virtual Reality in various aspects. The method in this study follows the Preferred Reporting for Systematic Reviews and Meta-Analysis (PRISMA). PRISMA was created with the aim of helping to ensure clarity and transparency of reporting, systematic reviews, and meta-analyses. The meta-analysis conducted resulted in the discovery of a large-size effect on the relationship between Virtual Reality and Safety. Based on the analysis with Jamovi, the results of the heterogeneity study obtained a value of Q = 170.487, a value of I2 = 96.25%, and Tau2 = 0.3825 (with SE = 0.1937). In addition, the effect size value is 0.67 (RE Model), the Eggers Regression value is -2.104, and in the forest plot image, it is known that the data represented by black dots are located inside the white triangle and are around the triangle.